肺腺样囊性癌4例病例报告 (Zhongguo Fei Ai Za Zhi, 2017)
BACKGROUND AND OBJECTIVE: Lung adenoid cystic carcinoma is a kind of rare lung cancer. Diagnosis and treatment is not enough understandable for them. We collected and analyzed 4 cases of lung adenoid cystic carcinoma for broadening the sight of this disease. METHODS: Retrospectively analysed the 4 cases we collected from Hunan Cancer Hospital Between January 2012 and December 2016. We depicted the pathology, immunohistochemical, epidermal growth factor receptor (EGFR) mutation and anaplastic lymphoma kinase (ALK) arrangement in these cases. And the methods of the diagnosis and treatment were analyzed. RESULTS: Lung adenoid cystic carcinoma is usually located in the airway, EGFR mutation and ALK arrangement is rare in this disease. Generally the metastasis of the lung cancer occurred in the advanced stage. The prognosis is good if the mass could be resected completely. CONCLUSION: Diagnosis of the lung adenoid cystic carcinoma depends on pathological experiments, surgery is the main treatment in the early stage, radiotherapy and chemotherapy is an advisable therapy in the advanced stage. And the prognosis of this kind of lung cancer is better than small cell lung cancer and non-small cell lung cancer.